Teachers’ perceptions of the impact of COVID-19 pandemic and virtual teaching on the physical and mental health of children in Kashmir: A qualitative study - Khalid Bashir; Zeenat Kausar; S. Muhammad Salim Khan; Mariya Amin Qurieshi; Inaamul Haq (Indian Journal of Psychiatry)
Background: Children inherently want to remain engrossed in the activities as easily as possible within their ecological environment and academic curricular ambit. Covid-19 adversely affected our physical, social, and mental conditions and children were no exception. Objectives: To understand the experiences of teachers who have been doing virtual teaching to children during COVID-19; To understand the impact of virtual teaching and COVID-19 on physical and mental health of children. Materials and Methods: The qualitative study was conducted in the Kashmir valley and school teachers teaching students from class Ist to class 8th were involved in the study. Participants were selected purposefully based on the inclusion criteria. One-to-one in-depth interviews were conducted with sixteen (16) school teachers, using a preformed interview guide. Data analysis was performed using the thematic analysis method. Results: Data analysis yielded four overarching themes and twelve subthemes viz:- 1) Attitudes towards online sessions among teachers (2) factors affecting the physical and mental health of children (3) Effectiveness of online classes for individual lines of children’s mental development (4) External and internal factors impacting child development and pedagogy. Conclusion: The study result explicitly showed mental and physical health of children got considerably affected by online teaching during the Covid-19 pandemic. Online teaching especially to children is less yielding in terms of effective academic consequences. Nevertheless, blending online teaching with pedagogy can enhance certain multidimensional capabilities of the children.